Der Übergangszustand der bimolekularen Eliminierung (E2-Reaktion) aufgrund neuerer kinetischer Isotopeneffektstudien - Alfred V. Willi (CHIMIA)
A discussion of the concerted E2 mechanism is presented with special emphasis on the model of the variable transition state. Sufficient evidence for the concertedness is based on primary β-hydrogen and α-heavy atom kinetic isotope effects. For various E2 reactions, results of experimental studies of primary β-H and α-N as well as secondary α-H and hydroxide-H isotope effects are compiled. Conclusions are drawn concerning the effect of reactant structure on relative degrees of Cα-X and Cβ-H bond breaking in the transition state. Special attention is given to the influence of remote substituents on the transition state geometry. The findings are discussed with the aid of a qualitative model of the potential energy surface.